DISTINCTIVE FEATURES OF DIAGNOSTICS, TREATMENT AND PREVENTIVE MEASURES OF PATHOLOGICAL SCARS OF MALLIOFACIAL AREA - V.V. Nahaychuk; L.I. Shkilniuk (Ukrainian Medical Stomatological Academy, 2017)
Health and beauty of human skin in the modern world is one of the main features of attractiveness of both women and men. Skin is the largest organ of the human body, depending on the age, height and weight its area is from 1.7 to 2.6 m2, and weight is about 16% of the total body weight. As a reflection of internal human health, it also protects the human body from exposure to adverse environmental factors: mechanical, chemical, thermal, microbiological, which leave their marks (scars, sword cuts) on it. According to the latest statistical data published in modern scientific publications, pathological scars are found in 10% of the total population of the world's population. Literature review shows that after various surgical manipulations pathological scarring occurs within the range from 39 to 68%, and after burn injuries - from 33 to 91%. Over the past two decades in the medical literature there have been many publications that greatly complemented the existing ideas about distinctive features of wound healing, formation, clinical course and treatment of scars. However, lots remains both obscure and controversial concerning a number of major issues. Vancouver scar scale is most commonly used for an objective assessment of tissues changed by the scars, evaluation criteria of which the clinical features in the area of the scar; ultrasound diagnosis; doppler flowmetry; determination of color intensity using a special color scale; plane geometry; local thermometry; pathological-morphological studies, spiral computed tomography and others. Complex preventive measures and treatment of scar lesions of the head and neck have a large number of therapeutic interventions and surgery. All methods of treatment for scars can be divided into surgical, conservative (medicinal and physical), and combined. Today the leading method of treatment for scarring is still surgery. Much attention is paid to the surgical technique to carry out surgeries, the method for the connection of wound edges, choice of suture material, prevention of purulent-inflammatory processes. But, unfortunately, relapse after surgical correction is observed in 55-68% of cases, and after the isolated surgical excision of keloid scars the relapse rate ranges from 50 to 100%. That is why together with some success of surgical treatment and local drug therapy of wounds, the interest to their non-drug treatment significantly increased. Today, more often the attention of specialists is attracted by physiotherapy techniques such as electrophoresis, phonophoresis, ultraphoresis, UFO, dermotonia, paraffin therapy, galvanophoresis. Treatment of pathological scars, especially keloid scars, is very challenging. The main condition for successful treatment of pathological scars is their prevention. So, the key role in achieving the desired aesthetic results of the treatment should be taken by preventive measures of scarring. Thus, the improvement of existing and search for new methods of prevention of pathological scarring is an urgent task of modern cosmetology, dermatology, combustiology, maxillofacial and plastic surgery.